Importance of Biological Properties of Winter Wheat in Cultivation - Ma'murakhan, Atabayeva; qizi, Dadajonova Zilola Shukurbek (American Journal of Biology and Natural Sciences, 2024)
Currently, the total area is 235.9 million in more than 132 countries of the world. Wheat is grown on more than 100,000 hectares, and the total yield is 755.2 million. tons. In 2021, wheat was grown on more than 1 million hectares of land in our republic. A comfortable temperature for seed germination is 12-20.